Pengelolaan Retribusi Pasar Soreang Dalam Peningkatan Pendapatan Asli Daerah Kabupaten Takalar - Hikmah, Nurul; Madani, Muhlis; Tahir, Nurbiah (Universitas Muhammadiyah Makassar, 2022)
This study purposed to find out the management of the afternoon market retribution in increasing local revenue in Takalar Regency. This study used qualitative with descriptive research type. Data collection techniques were observation, document and interview . The number of informants was 9 people. Data collected from various sources to obtain sufficient data. The data were analyzed qualitatively through organizing the data, describing it into units, describing it into words and sentences and then making conclusions. The results of this study showed that the management of retribution in the afternoon market was quite good, because the withdrawal of retribution in the afternoon market has begun to stabilize. However, there were still obstacles faced by the cooperative, SME and trade offices of Takalar Regency in maximizing the achievement of retribution receipts such as the lack of accurate actual data about the potential of the afternoon market, the discipline of retribution collectors in carrying out their duties, the salary system was often late and less supervision because it relied on monthly reports only.Keywords: Management, Market Retribution, Improvement